Phytotoxic property of metabolites isolated from Garcinia gardneriana. (June 2021) - Rodrigues, Dayana A.; de Sousa, Bianca L.; da Silva, Júnio G.; Pereira, Gustavo A.M.; Bousada, Guilherme M.; da Silva, Antonio A.; Demuner, Antonio J.; Costa, Éderson D'M.; Pilau, Eduardo J.; Silva, Evandro; dos Santos, Marcelo H.
Graphical abstract: Highlights: 7-epiclusianone, guttiferone-A and fukugetin were isolated from Garcinia gardneriana . Phytotoxic activity by guttiferone-A is higher to commercial herbicide glyphosate. Guttiferone-A interacts effectively with transferase enzymes type. Development of new agrochemicals. Abstract: Garcinia gardneriana is a medicinal tree species used in Brazil in the treatment of hepatitis and gastritis. This use is attributed to phenolic compounds, mainly 7-epiclusianone, guttiferone-A and fukugetin, which present several proven biological activities. However, to the best of our knowledge, no study on the phytotoxic activity of G. gardneriana extracts has been conducted until now. This research proposed to isolate and quantify by high-performance liquid chromatography (HPLC) the major compounds from G. gardneriana seed extracts in ethyl acetate and to evaluate their phytotoxic activities. The natural products 7-epiclusianone, guttiferone-A and fukugetin were quantified at concentrations varying from 0.46 to 1.13 mg mL −1 and were isolated with yields ranging from 7% to 23% (w/w). The phytotoxic assay indicated that the crude extract showed no action on the dry matter of Sorghum bicolor plants, but the isolated compounds fukugetin and 7-epiclusianone had moderate activity. On the other hand, guttiferone-A displayed a greater herbicide activity than glyphosate, a positive control, even in almost three times lower concentrations, causing severe intoxication in the plants. This work is the first report on this activity by the extract of G. gardneriana and its isolated compounds. Besides that, guttiferone-A showed up as a scaffold for the development of new agrochemicals. Complementing these findings, computational studies suggested that this benzophenone can interact effectively with transferase enzymes type, in special caffeic acid O -methyltransferase from S. bicolor (PDB code: 4PGH), indicating a possible mechanism of action in this plant.